Standardization of Information Security Management in the Banking Sector using the ISO 27001:2022 Framework - Ryanto, Kamil; Tundjungsari, Vitri (Newinera Publisher, 2024)
This research discusses evaluations related to cyber security standardization in the banking sector at Bank Victoria International Tbk using qualitative methods and data collection techniques, interviews and focus group discussions. The focus of this research is evaluation related to Data Leaks, Threats of Attacks from outside, and Policies for preventing cybercrime in banking using the ISO 27001:2022 Framework. The location of this research was carried out at Bank Victoria International Tbk. The location for this research was chosen because Bank Victoria is one of the banks that is currently carrying out a preventive implementation process in preventing cybercrime by implementing ISO 27001:2022 related to Cyber Security. The problems that will be explained in this thesis research are First, how does PT. Bank Victoria is taking precautions regarding data leaks using the ISO 27001:2022 framework (1). Second, how does PT Bank Victoria carry out monitoring and monitoring related to external threats or attacks that could harm the bank using the ISO 27001:2022 framework (2). Third, how to comply with procedures, policies or regulators related to process flow and security controls for the use of information technology at PT. Bank Victoria uses the ISO 27001:2022 Framework (3). The conclusion of this research is that Bank Victoria International Tbk is still in the stage of improvement in terms of cyber security, although currently PT Bank Victoria is showing good preventive measures by forming a special organizational structure to handle legality issues and implementing cybercrime prevention applications, but this has not been stated in the Policy.